Carbazole substituted BODIPY dyes: Synthesis, photophysical properties and antitumor activity. (December 2015) - Sengul, Ibrahim F.; Okutan, Elif; Kandemir, Hakan; Astarcı, Erhan; Çoşut, Bünyemin
Abstract: In this study, two different BODIPYs containing carbazole groups at the meso position were designed and synthesized. All compounds were fully characterized by elemental analysis, FT-IR, matrix-assisted laser desorption/ionization time-of-flight mass spectrometry, 1 H and 13 C NMR spectroscopy. The photophysical properties of the new compounds were investigated by means of absorption and fluorescence spectroscopies in dilute dichloromethane solutions. We were also interested in the biological activity of these two novel carbazole-linked BODIPYs, particularly concerning their ability to inhibit human colon cancer HT29 cell lines. The photophysical studies revealed strong donor–acceptor interaction between carbazole and BODIPY and follow the order compound 5 > compound 4. Also, preliminary assay showed that compound 5 possessed higher cytotoxic activity than compound 4, with IC50 values of 8.3 ng/mL and 21.7 ng/mL respectively. Graphical abstract: Highlights: New carbazole substituted BODIPYs have been synthesized. The photophysical properties of the compounds have been studied in dichloromethane. Their ability to inhibit human colon cancer HT29 cell lines have been investigated. Enhanced FRET was noted for some molecules.